Integrative single-cell analysis of longitudinal t(8;21) AML reveals heterogeneous immune cell infiltration and prognostic signatures - Li, Xue-Ping; Song, Jiang-Tao; Dai, Yu-Ting; Zhang, Wei-Na; Zhao, Bai-Tian; Mao, Jia-Ying; Gao, Yan; Jiang, Lu; Liang, Yang (Frontiers in Immunology, 2024)
Immunotherapies targeting T cells in solid cancers are revolutionizing clinical treatment. Novel immunotherapies have had extremely limited benefit for acute myeloid leukemia (AML). We characterized the immune microenvironment of t(8;21) AML patients to describe its heterogeneity and determine how immune cell infiltration status influences prognosis. Through multi-omics studies of primary and longitudinal t(8;21) AML samples, we characterized the heterogeneous immune cell infiltration in the tumor microenvironment and their immune checkpoint gene expression. CD8+ T cells were enriched and HAVCR2 and TIGIT were upregulated in the CD34 + CD117 dim %-High group; these features are known to be associated with immune exhaustion.Data integration analysis of single-cell dynamics revealed that a subset of T cells (cluster_2) (highly expressing GZMB, NKG7, PRF1 and GNLY) evolved and expanded markedly in the drug-resistant stage after relapse. External cohort analysis confirmed that the cluster_2 T-cell signature could be utilized to stratify patients by overall survival outcome. In conclusion, we discovered a distinct Tcell signature by scRNA-seq that was correlated with disease progression and drug resistance. Our research provides a novel system for classifying patients based on their immune microenvironment.